Cost-effective FRP solutions for enhancing strength and strain of sustainable concrete made with waste tyre rubber - Panumas Saingam; Burachat Chatveera; Qudeer Hussain; Gritsada Sua-iam; Preeda Chaimahawan; Chisanuphong Suthumma; Afaq Ahmad (Scientific Reports, 2026)
= 0.84-0.99) between predicted and experimental data. The derived regression-based formulations successfully captured the influence of confinement pressure, rubber content, and wrapping configuration. These findings demonstrate that GFRP provides an economical and sustainable confinement solution for enhancing the performance of rubberized concrete in structural and retrofitting applications.
Keywords: Structural Behavior of Reinforced Concrete; Innovative concrete reinforcement materials; Asphalt Pavement Performance Evaluation